HUBUNGAN FORGIVENESS DENGAN HAPPINESS PADA ANAK USIA SEKOLAH - REMAJA DI PANTI ASUHAN ANUGERAH KASIH ABADI MEDAN ESTATE - Agukguk Manalu; Dior Manta Tambunan (Universitas Murni Teguh, 2026)
Orphanages are social institutions that have service programs that meet the needs of the community to solve social problems, especially poverty, ignorance, and the problems of orphans and abandoned children that are developing in the community. Children are the most important asset for the progress of the nation because they are the next generation who are fighting to face future challenges This type of research is quantitative with a cross-sectional survey research design. The sampling technique in this study was Total Sampling, but when the study was carried out with 56 respondents who attended, the sample in this study amounted to 56 respondents. Data analysis used a parametric test of Pearson correlation. The results of this study with the Pearson correlation test showed that there was a significant relationship between forgiveness and happiness with a p-value = 0.046 (α<0.05). It is recommended for future researchers to add other variables related to forgiveness and happiness such as religiosity, meaning of life, self-acceptance and subjective well-being.